Challenging the ischemic core concept in acute ischemic stroke imaging - Goyal, Mayank; Ospel, Johanna M.; Menon, Bijoy; Almekhlafi, Mohammed; Jayaraman, Mahesh; Fiehler, Jens; Psychogios, Marios; Chapot, Rene; van der Lugt, Aad; Liu, Jianmin; Yang, Pengfei; Agid, Ronit; et al. (Stroke, 2020)
Endovascular treatment is a highly effective therapy for acute ischemic stroke due to large vessel occlusion and has recently revolutionized stroke care. Oftentimes, ischemic core extent on baseline imaging is used to determine endovascular treatment-eligibility. There are, however, 3 fundamental issues with the core concept: First, computed tomography and magnetic resonance imaging, which are mostly used in the acute stroke setting, are not able to precisely determine whether and to what extent brain tissue is infarcted (core) or still viable, due to variability in tissue vulnerability, the phenomenon of selective neuronal loss and lack of a reliable gold standard. Second, treatment decision-making in acute stroke is multifactorial, and as such, the relative importance of single variables, including imaging factors, is reduced. Third, there are often discrepancies between core volume and clinical outcome. This review will address the uncertainty in terminology and proposes a direction towards more clarity. This theoretical exercise needs empirical data that clarify the definitions further and prove its value.
Gesehen am 13.11.2020